QUALITY RISK MANAGEMENT – CAPA TO PREVENT POTENTIAL QUALITY ISSUES - Jain, Sanjay Kumar (Asian Journal of Pharmaceutical Research and Development, 2017)
In the pharmaceutical industry there are number of risks and failure involved in each and every pharmaceutical product throughout the life cycle. Risk are managed in our day to day life and ensure that preventive measures are taken to avoid any hazards in our life, similarly quality risk management is the tool using which potential quality issues can be avoided to occur for the pharmaceutical products throughout the lifecycle of the product. The principle of QRM can be applied proactively or retrospectively at many stages of pharmaceutical quality such as product development, technology transfer, production, pharmacokinetic evolution, distribution, inspection, validation, submission/review process and life cycle management in product development. It finds useful application in selection of raw materials, solvents, excipients, packaging and labelling materials, formulation development, process development and process improvement. This article discusses general principles and several tools for risk management which can be used successful to identify the potential quality issues. The quality risk management theory and applications for controlling the risk to pharmaceutical quality has identified various potential quality issues and allowed the pharmaceutical industry to manufacture the quality and safe products for the patients.